1991
DOI: 10.1021/bk-1991-0467.ch010
|View full text |Cite
|
Sign up to set email alerts
|

New Fluorocarbon-Containing Hydrophobically Associating Polyacrylamide Copolymer

Abstract: The synthesis of polyacrylamide copolymers containing fluorine-containing acrylates 1, 2, 4 or 5 or silicone-containing methacrylate 6 was carried out by emulsion polymerization using persulfate as initiators and ionic perfluoro surfactants. The Brookfield viscosities of these copolymers, especially those containing 1 or 2, were much higher than the laurylacrylate (3) containing co polymer. The comonomer content of the 1 or 2 containing copoly mers that were most strongly viscosifying was only .07-.28 mole per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The study of associative polymers has recently drawn considerable interest due to their unusual rheological properties,1–3 which are due to the presence of incompatible4–7 groups, for example, hydrophilic and hydrophobic groups, and/or to the strong intermolecular association, ie hydrophobic association of one of the groups. The elucidation of structure–properties relationships of these associative polymers8–12 requires well‐defined polymer structures.…”
Section: Introductionmentioning
confidence: 99%
“…The study of associative polymers has recently drawn considerable interest due to their unusual rheological properties,1–3 which are due to the presence of incompatible4–7 groups, for example, hydrophilic and hydrophobic groups, and/or to the strong intermolecular association, ie hydrophobic association of one of the groups. The elucidation of structure–properties relationships of these associative polymers8–12 requires well‐defined polymer structures.…”
Section: Introductionmentioning
confidence: 99%
“…A maximum of efficiency was observed with POE with a degree of polymerization close to 500 (M n ) 20 000). 16 Hogen-Esch et al have reported that perfluoroalkylmodified water-soluble polymers (hydroxyethylcellulose, 14 polyacrylamides, 8,18 or POE 19 ) are much more effective thickeners compared to the corresponding hydrocarbon derivatives. The enhanced viscosity can be explained by the clustering and self-assembling of the perfluorinated groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that perfluoroalkyls are more hydrophobic than their hydrocarbon analogues. 27 Because of this, Zhang et al [28][29][30] studied copolymers based on polyacrylamide with a small amount of an acrylate or methacrylate with a fluorocarbon-containing group. Such polymers exhibited more pronounced hydrophobic association than the corresponding hydrocarbon-substituted copolymers.…”
Section: Introductionmentioning
confidence: 99%